1990
DOI: 10.1002/nur.4770130403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate and low intensity long‐term exercise by older adults

Abstract: The goal was to determine the existence of differential effects of long-term moderate- or low-intensity exercise on selected bio-behavioral variables in 72 community-dwelling persons over 60 years of age. After screening, subjects were randomly assigned to a moderate (n = 39, 60-70% heart rate reserve [HRR]) or low (n = 33, 30-40% HRR) intensity exercise protocol. Both groups exercised three times per week for 9 months and dependent measures were taken at baseline, 4.5 months and after 9 months. Repeated measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 26 publications
3
64
0
1
Order By: Relevance
“…Eight papers were excluded after all, because of the following reasons, no full-text paper (n=1); no RCT (n=1); study population also including subjects with depression and psychosis (n=1); multi-component intervention including non-exercise components (n=2); no neuropsychological tests (n=2); or describing same study and results as another included study (n=1). Finally, 23 papers were included; 15 among subjects without cognitive decline (No Cognitive Decline = NCD) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and eight among subjects with cognitive decline (CD).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight papers were excluded after all, because of the following reasons, no full-text paper (n=1); no RCT (n=1); study population also including subjects with depression and psychosis (n=1); multi-component intervention including non-exercise components (n=2); no neuropsychological tests (n=2); or describing same study and results as another included study (n=1). Finally, 23 papers were included; 15 among subjects without cognitive decline (No Cognitive Decline = NCD) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and eight among subjects with cognitive decline (CD).…”
Section: Study Selectionmentioning
confidence: 99%
“…In eight studies, the outcome assessor was blinded (NCD 33, 35, 36 and CD 41,42,44,45,47 ). Participants were blinded in two studies, one among cognitively healthy adults 38 and one in subjects with cognitive decline. 47 The exercise trainer was blinded in two studies as well (NCD 31 and CD…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…47,55,57,[59][60][61][62][63][64] One explanation may be that most exercise programs last a few months, whereas physical activity may protect cognitive function in the long-term.…”
Section: Physical Activity and The Prevention Of Dementia Ad Or Cogmentioning
confidence: 99%
“…Randomized, controlled studies have also demonstrated the numerous benefits of exercise training in older adults including improvcments in cardiorespiratory and metabolic function (Braith et al, 1994), lipid profile , flexibility, balance (Brown & Holloszy, 1993), psychological and cognitive functioning (McMurdo & Burnett, 1992), and sleep patterns (Stevenson & Topp, 1990). Reported changes in cardiovascular fitness indicators for previously sedentary older individuals include lowered resting pulse, decreases in cardiac output (e.g., BP and heart rate) during high intensity exercise, and increased maximal aerobic power (V02 Max) Steinhaus et al, 1990).…”
Section: Benefit3 Of Exercise Therapymentioning
confidence: 97%